(untitled) (Medical Forum Monthly, 2024)
Objective: In order to measure the success, safety and aesthetic results of the nasolabial flap for reconstruction of orofacial defects at CMH Rawalpindi. Study Design: A Cross sectional study Place and Duration of Study: This study was conducted at the at Plastic Surgery Department Combine Military Hospital, Rawalpindi from November 2023 to April 2024. Methods: A cross-sectional study employing 150 patients of CMH Rawalpindi who had nasal labial flap reconstruction from November 2023 to April 2024. Evaluation was conducted on flap success rate, flap complications, functional score achieved and aesthetic score given by the patients. Categorical data was analyzed using frequency tables and chi-square method of data analysis while independent variable measurements was analyzed using mean and standard deviations p value results from the analysis were used to judge the significance of the results. Results: Out of 150 patients, 100 were males and 50 females with the group’s mean age of 45.5 ±12.3. Flap coverage was successful in 95 % of the cases. The flap survival average was 98%, with a minor complication rate of 8, significant at p < 0.05. Esthetic outcomes were assessed as highly satisfactory, mean = 27.6; sd = 1.2 for patient satisfaction. Functionally, the majority of the patients maintained normal oral competence after reconstruction in 92% of the cases. Conclusion: Using human data, the authors described the nasolabial flap as the option offering high OR rates, low complications, and good functional/aesthetic result in the reconstruction of the orofacial defects. However, todate it is still used as an important modality in facial reconstructive surgery.